RESEARCH OF THE MODEL THE TREATMENT REQUESTS TO DATABASE IN ANYLOGIC - Шаталова, Юлия Георгиевна (Eastern-European Journal of Enterprise Technologies, 2012)
The models of interaction of clients and distributed database are analyzed. The choice of a three-level model is proved. We construct a simulation model in AnyLogic for study the characteristics of the model.